The Principle of the Presumption of Continuity (Istiṣḥāb): A Comparative Study of Its Formation, Evolution, and Scope of Application in the Principles of Jurisprudence in Islamic Sects - Muhammad Nozari; Ali Mahdavi (پژوهش‌های فقهی مسائل مستحدثه)
Istiṣhāb (presumption of continuance), a concept frequently addressed in the principles of Islamic jurisprudence (Uṣūl al-fiqh), involves a jurist resorting to it as a legal basis for their ruling when unable to find a specific Sharīah ruling in the four recognized sources. The current historical investigation examines the origins of Istiṣhāb within Islamic traditions, drawing from primary sources of both Shia and Sunni scholars, highlighting their contributions and influence in shaping and advancing this principle as a significant component of the science of jurisprudential principles. Through a library research methodology, the study concludes that the initial application of the principle of Istiṣhāb emerged within Sunni scholarly circles. However, despite its early introduction, it experienced a stagnation in its scholarly progression. Conversely, the trajectory of Shia scholars' engagement with Istiṣhāb follows an upward trend. Initially adopting the principle from Sunnis, they then modified it based on their own religious principles, establishing comprehensive definitions and widely accepted jurisprudential practices. This movement persists to the present day.